Africa's development in the twenty-first century : pertinent socio-economic and development issues - Konadu-Agyemang, Kwadwo; Panford, Martin Kwamina (Aldershot, England ; Burlington, VT : Ashgate, 2006)
Provides a multidisciplinary exploration of the continent's development opportunities and challenges in the 21st century.
16. Transportation as a factor in the socio-economic development of Ghana / Sesime Adanu -- 17. Gender disparities in African education : some socio-economic implications for Africa's development in the 21st century / Kwadwo Konadu-Agyemang and Judith Shabaya -- 18. The politics and apolitics of development : the case of a development project in Northern Ghana / Karl Botchway -- 19. Currency devaluation and poverty in Mauritania / Mohameden Ould-Mey -- 20. Changing urban development : Africa's opportunities and challenges in a global economy at the dawn of the 21st century / Richard Grant -- 21. Africa's participation in the revolution in information and communications technology : opportunity for economic development or deprivation? / Peter A. Kwaku Kyem and Olivia Kyem -- 22. Making change : reinventing Africa for the 21st century / Kwamina Panford and Kwadwo Konadu-Agyemang.
Includes bibliographical references and index.
Keywords: Prognose; 2000-2099; Economic development -- Social aspects; Economic development -- Social aspects; Economic history; Politics and government; Social conditions; Soziale Situation; Wirtschaftliche Lage; Wirtschaftsentwicklung; Wirtschaft; Entwicklung; Sociaal-economische ontwikkeling; Ontwikkelingseconomie; economic and social development; political development; regional development; development policy; globalization; economic integration; ECOWAS; food security; land reform; poverty; gender and development; Economic development -- Social aspects; Economic development -- Africa; 2; 2; 2; 2; mondialisation; 2; CEDEAO; 2; 2; 2; 2; 2; 2; desarrollo regional; 2; 2; 2; CEEAO; seguridad alimentaria; reforma de la tenencia de la tierra; pobreza; 2; Africa -- Economic conditions -- 21st century; Africa -- Social conditions -- 21st century; Africa -- Politics and government; Afrique -- y; Afrique -- Conditions sociales; Afrique -- Politique et gouvernement; Africa; Afrika; Afrika; Africa; Africa -- Economic conditions -- 21st century